Double set up technique as a bailout of diagonal branch coronary perforation: a case report - Syukri, Muhammad; Yanni, Mefri; Syafri, Masrul; Phalguna, Shindu; Firmansyah, Alles; Indah, Merlin Sari Mutma; Mahendra, Ivan; Zulkarnain, Hadi (Medical Journal of Indonesia, 2024)
Coronary artery perforation is a rare but potentially life-threatening complication of percutaneous coronary intervention (PCI). A 55-year-old male with a history of implanted stent on the left main ostium to the proximal left circumflex artery (LCX) and distal right coronary artery, and chronic total occlusion (CTO) on ostium left anterior descending (LAD). PCI was performed using a stiff wire to cross the CTO body in LAD. We performed an injection and confirmed the presence of extravasation. We successfully managed to stop the bleeding by placing the tips of floppy wire that were cut into pieces. A drainage pathway was made through thoracotomy for pericardial effusion. Angiography showed persisting extravasation at the wire insertion site. We then made our own covered stent. We implanted on the osteal LAD until proximal LCX. Repeated angiography showed no contrast extravasated from the perforation site, and the patient was stabilized and discharged.